A Newtonian Ontological Model Resolving Wave-Particle Duality - Bajpai, Amit (Journal of Research in Vocational Education, 2025)
Augmented Newtonian Dynamics (AND) is a modified framework for understanding the behavior of particles within classical mechanics, extending traditional Newtonian dynamics by incorporating interactions that arise from the quantum vacuum. In this theory, the vacuum is not an empty void but a dynamic medium that influences particle motion through transient fluctuations. These fluctuations, although imperceptible at macroscopic scales, result in brief yet significant interactions that modify the trajectories and stability of particles. At the core of AND is the idea that particles, while orbiting the nucleus, continuously engage in short-lived, localized interactions with the vacuum. These interactions exert forces on the particles that are strong enough to influence their motion yet occur over such brief time scales that they do not violate macroscopic conservation laws of energy and momentum. This subtle yet persistent interaction with the vacuum provides a stabilizing effect on the motion of particles, preventing phenomena such as the collapse of orbital systems or rapid energy dissipation, which would otherwise be expected in classical mechanics. By integrating these vacuum-based forces into the classical framework, Augmented Newtonian Dynamics offers a new perspective on particle motion, one that accounts for stability in systems where classical mechanics would traditionally predict instability. The theory posits that these interactions, while small in their instantaneous effects, accumulate over time to produce stable, self-correcting dynamics for particles in various systems, leading to observable phenomena that diverge from traditional Newtonian predictions without invoking additional classical forces.